"Hopes and wishes": Goals of high-need, high-cost older patients and their caregivers. Issue 7 (July 2020) - Wyman, Mary F.; Liebzeit, Daniel; Voils, Corrine I.; Bowers, Barbara J.; Chapman, Elizabeth N.; Gilmore-Bykovskyi, Andrea; Kennelty, Korey A.; Kind, Amy J.H.; Loosen, Julia; Rogus-Pulia, Nicole; Dattalo, Melissa
Highlights: There is limited research on patient goals of "high-need, high-cost" older patients. Qualitative analysis identified eight distinct goal categories of these patients. Caregivers of HNHC older patients provide critical information regarding goals. Findings can support shared decision making and inform the development of effective care models. Abstract: Objective: Integration of patient-identified goals is a critical element of shared decision-making and patient-provider communication. There is limited information on the goals of patients with multiple medical conditions and high healthcare utilization. We aimed to identify and categorize the goals described by "high-need, high-cost" (HNHC) older patients and their caregivers. Methods: Using conventional content analysis, we used data from interviews conducted with 17 HNHC older patients (mean age 72.5 years) and 4 caregivers. Results: HNHC older patients and their caregivers used language such as "hopes, wishes, and wants" to describe their goals, which fell into eight categories: alleviating discomfort, having autonomy and control, decreasing treatment burden, maintaining physical functioning and engagement, leaving a legacy, extending life, having satisfying and effective relationships, and experiencing security. Conclusion: Our results contribute to knowledge of goals of HNHC patients and provides guidance for improving the patient-provider relationship and communication between HNHC older patients and their healthcare providers. Practice implications: Our findings can inform provider efforts to assess patient goals and engage high-need, high-cost older patients in shared decision-making. Further, this study contributes to an improved understanding of HNHC older patients to support continued development of effective care models for this population.